Knowledge, attitude and practice (KAP) of earthquake preparedness amongst the elderly in risk areas: Chiang Rai, Thailand - Tanika Songlar; Nicharuch Panjaphothiwat Pussadee La-or; Chalitar Chomchoe; Siriyaporn Khunthason (College of Public Health Sciences, Chulalongkorn University, 2019)
Purpose - Chiang Rai being an earthquake-prone city, it is essential to raise awareness about earthquake safety and readiness, especially amongst the elderly population who spend most of their time at home. The purpose of this paper is to evaluate the earthquake preparedness of elders in relation to knowledge, attitude and practice. Design/methodology/approach - This was an analytic cross-sectional study. Research data were collected from 480 elders of 60 years old and above. The research instruments were questionnaires about knowledge, attitude and self-assessment of practices in earthquake situations. Data were analyzed by number, percentage and a χ2 test. Findings - Of participants interviewed, 39.4 percent were aged between 60 and 66 years old. Overall, 94.0 percent of them had already experienced an earthquake, with 79.4 percent having experienced it in 2014. Participants had a good level of knowledge and attitude toward earthquake safety. Their practices toward earthquake readiness, however, were insufficient due to the lower practice scores (<12), especially found in the high seismic zone. The score level of knowledge, attitude and self-assessment of practice in earthquake situations showed that there is a difference in statistical significance (p<0.05). Originality/value - This study focuses attention on the need to increase levels of preparedness. Safety instructions and earthquake drills should be promoted and supported in order to prepare elders for an earthquake in the study area. Research findings identified in this study will help to address the specific needs of the elderly when implementing an earthquake disaster risk reduction plan.